Digital Da’wah Strategy for Generation Alpha: Case Study - Zuhdi, Ahmad; Yusuf, Fakhri; Zulfikar, Zulfikar; Costa, Tiago; Malintang, Jimmy (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The rapid advancement of digital technology has transformed the landscape of Islamic preaching (da’wah), particularly in engaging Generation Alpha, a demographic deeply immersed in digital platforms. Traditional da’wah methods, which rely on face-to-face interactions and textual resources, are less effective in reaching this tech-savvy generation. Digital da’wah strategies must be adapted to align with the media consumption habits, cognitive preferences, and interactive engagement styles of Generation Alpha. Understanding the effectiveness of digital platforms in delivering Islamic teachings is crucial for optimizing contemporary da’wah efforts. This study aims to analyze the effectiveness of digital da’wah strategies in engaging Generation Alpha by examining content formats, platform choices, and interaction models. A qualitative case study approach is employed, incorporating in-depth interviews with digital da’wah practitioners, content analysis of online Islamic educational materials, and audience engagement metrics. Findings reveal that short-form videos, gamification, and interactive storytelling significantly enhance engagement and message retention among Generation Alpha. Social media platforms such as YouTube, TikTok, and interactive learning apps emerge as the most effective channels for digital da’wah. The study concludes that Islamic content must be visually engaging, concise, and interactive to maintain relevance in the digital era. Recommendations for optimizing digital da’wah strategies for Generation Alpha are discussed.